Bibliographic summary about aquatic parasitoids - Carlos Henrique Marchiori (Annals of Marine Science - Peertechz Publications, 2020)
Parasitoids are responsible for reducing the populations of insects that proliferate on various substrates. Evaluation of these species for natural control over these insects is important for enabling studies that aim towards subsequent selection of species for use in biological control programs. This manuscript consists of the elaboration of a bibliographic summary of the parasitoids of Parasitica Hymenoptera) collected in aquatic environments. A bibliographic research was carried out that contained published works on the following aspects: The conservative, Parasitic Hymenoptera characteristics, main superfamilies and families and studies carried out and main genera or species, from November 2019 to January 2020. All species of aquatic parasitoids belong to the order Hymenoptera.